Comentarios al Anteproyecto de Ley Orgánica de igualdad de hombres y mujeres - Figueruelo Burrieza, Ángela (2023)
On March 3 rd 2006 the Spanish Council of Ministers passed the Draft Law on Gender Equality (Anteproyecto de Ley Orgánica de Igualdad entre Mujeres y Hombres). The Draft develops the different European Directives related to gender equality. It contains everything established in previous Spanish regional laws on real and effective gender equality and in the jurisprudence of the Spanish Constitutional Court and the European Court of Justice. This Draft intends to complete the formal equality of the principle of equality before the law contained in the Spanish constitution (Article 14). It wants to achieve material equality, also contained in the Spanish Constitution (Article 9.2). In spite of the demographic importance of women, Laws are necessary to achieve real and effective equality that eradicates gender violence, salary discrimination, high levels of unemployment, the scarce presence of women in leading economic, political and social positions, etc.